2006
DOI: 10.2174/138620706776843237
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Creation of Novel Proteins by Block Shuffling

Abstract: We have been investigating the creation of novel proteins by means of block shuffling, where the term block refers to an amino acid sequence that corresponds to particular features of proteins, such as secondary structures, modules, functional motifs, and so on. Block shuffling makes it possible to explore the global sequence space, which is not feasible with conventional methods, such as DNA shuffling or family shuffling. To investigate what properties are required for the building blocks, we have analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 68 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…Following a related idea, it has been suggested that new enzymes can be generated by recombining different segments of modern proteins, and the concept has been shown to be successful. 4,23 Here we describe Systematic Catalytic Loop Exchange (SCLE), a new strategy for exchanging loops on a TIM barrel fold. As a scaffold, we chose a variant of phosphoribosylanthranilate isomerase (PRAI-LoxP) from Escherichia coli, a monomeric enzyme where we have previously done significant work.…”
Section: Introductionmentioning
confidence: 99%
“…Following a related idea, it has been suggested that new enzymes can be generated by recombining different segments of modern proteins, and the concept has been shown to be successful. 4,23 Here we describe Systematic Catalytic Loop Exchange (SCLE), a new strategy for exchanging loops on a TIM barrel fold. As a scaffold, we chose a variant of phosphoribosylanthranilate isomerase (PRAI-LoxP) from Escherichia coli, a monomeric enzyme where we have previously done significant work.…”
Section: Introductionmentioning
confidence: 99%
“…When blocks including secondary structures such as α-helix or β-sheet were combined as "structural motifs", greater structure forming capability and enzymatic activity were found. 52,75,76 Recently, several methods have been developed to combine multiple DNA fragments without homologous sequences. Structure-based combinatorial protein engineering (SCOPE) employs chimeric primers to combine structural elements from different proteins that have similar folds but have a low level of sequence identity.…”
Section: Proteins By Copying and Shuffling Genesmentioning
confidence: 99%
“…In particular, I next focus attention on the application of mRNA display to the selection of functional proteins from fully randomized and partially randomized libraries with a limited set of amino acids, , and selection of functional proteins from block-shuffled libraries, which are constructed on the basis of the hypotheses described above. Such application of mRNA display allows the validity of the hypotheses to be evaluated in terms of the numbers of functional proteins obtained from these libraries.…”
Section: A Strategy For In Vitro Selection Of Functional Proteins By ...mentioning
confidence: 99%
“…The proposed robust adaptive design rules of natural selection also provide a systematic robust biochemical circuit design method of biochemical networks for drug design and robust engineered synthetic biocircuit design purposes in the future. We can use computational prediction and rational design ( Altamirano et al 2000 ; Johannes et al 2005 ; Tsuji et al 2006 ), directed evolution ( May et al 2000 ; Wang et al 2000 ; Yuan et al 2005 ) and dynamic controller ( Farmer and Liao, 2000 ; Bulter et al 2004 ) to quickly create a library of variants for artificial evolution to achieve the desired property of biochemical networks. Rational design and directed evolution are to modify the catalytic or binding property of an enzyme which corresponds to the changes of kinetic parameters g ij and h ij in the S-System model through modulating the enzyme structure and through DNA shuffling, respectively.…”
Section: Introductionmentioning
confidence: 99%